Pemberdayaan Masyarakat Nagari Palangki dalam Mengatasi Penyakit Mulut dan Kuku (PMK) - Tinda Afriani; Farez Fathoni Albadri; Ayu Sri Wahyuni; Ricky Adelin Simbolon; Muhammad Hamzah Fajri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
Nagari Palangki, IV Koto District, Sinjunjung Regency, is one area that has the potential for beef cattle farming and a large livestock market. The Palangki cattle market is the largest cattle market in West Sumatra. The Palangki cattle market has become a supplier of beef cattle for the provinces of West Sumatra, Jambi, Riau and Bengkulu. The operation of the Palangki livestock market was closed due to cattle infected by mouth and nail disease (FMD). FMD is a contagious animal disease that attacks hoofed animals, especially livestock such as cattle, goats and sheep caused by viruses. This disease can cause huge economic losses because it can lead to a decrease in livestock productivity and even death. It is necessary to take action in dealing with FMD, therefore socialization of the handling and prevention of oral and nail diseases is carried out to the Basung Indah Palangki farmer group. FMD vaccination was carried out in collaboration with the Agriculture Service of Sijunjung Regency and 100 cows were vaccinated in District IV Nagari. The activity aimed to empower and provide insight to Nagari Palangki cattle farmers in overcoming oral and nail diseases.